Knowledge and Practice of Clinicians regarding Syndromic Management of Sexually Transmitted Infections in Public Health Facilities of Gamo Gofa Zone, South Ethiopia. (29th October 2015) - Alemayehu, Addisu; Godana, Wanzahun
Abstract : Background . Sexually Transmitted Infections (STIs) are the leading causes of morbidity among young adults. This study assessed the knowledge and practice of clinicians regarding syndromic management of STIs in public health facilities of Gamo Gofa Zone, Southern Ethiopia. Methods . Facility based cross-sectional study with mixed methods of data collection was conducted in public health facilities of Gamo Gofa Zone. The study included 250 clinicians and 12 health facilities, 26 mystery clients were hired, and 120 STI patient cards were reviewed. Data was entered in EPI info version 7.0.1 and analyzed by SPSS version 20. Results . Of the participated clinicians, 32 (12.8%) were trained on syndromic management of STIs. Highest knowledge of clinicians was for urethral discharge (27.2%). Professional category of clinicians and type of health facility (AOR = 0.194; 95% CI = 0.092, 0.412) were determinants of urethral discharge knowledge. Of the cards reviewed, only in 8.3% of cards and 19.23% of mystery clients did the clinicians correctly follow the guideline. Conclusion . Knowledge and practice of clinicians regarding syndromic management of STIs in study area were poor. Efforts should be made to increase the knowledge of clinicians by providing training on syndromic management of STIs and supportive supervision should be regular.